Conserved architecture of RAD51 recombinase in ruminants revealed through molecular cloning and characterization - SONIKA AHLAWAT; REKHA SHARMA; REENA ARORA; LATIKA JAISWAL; MEENU CHOPRA; PRIYANKA SHARMA; SACHINANDAN DE (Indian Journal of Animal Sciences, 2016)
Meiotic recombination is a highly conserved process that ensures accurate segregation of homologous chromosomes and contributes to genetic variability of a species to with stand the pressure of natural selection. RAD51 recombinase plays a pivotal role in double strand break repair during homologous recombination and also ensures that chromosomal integrity is maintained during meiotic cell cycle. The present study was aimed to clone and sequence characterize RAD51 gene from cDNA isolated from testicular tissue of four ruminant species (buffalo, cattle, sheep and goat). The complete open reading frame of RAD51 gene was observed to be 1020 nucleotides in length encoding a putative protein of 339 amino acids. Functional feature prediction by SMART and Pfam revealed highly conserved DNA binding h4elix-hairpin-helix motif in the N terminal domain and Walker A and Walker B motifs in the catalytic domain which confer ATP binding and hydrolysis activity, respectively. All RAD51 orthologs and paralogs (RAD51B, RAD51C, RAD51D, XRCC2 and XRCC3) were subjected to phylogenetic analysis. Evolutionary analysis between the different orthologs and paralogs suggested that these proteins are conserved from yeast to humans since all the orthologs from different species clustered in their respective clade, clearly demarcating the paralogs. Gene duplication events have expanded the RAD51 family in eukaryotes offering them increased capacity to repair DNA and promote homologous recombination.